Scn1a gene reactivation after symptom onset rescues pathological phenotypes in a mouse model of Dravet syndrome - Nicholas Valassina; Simone Brusco; Alessia Salamone; Linda Serra; Mirko Luoni; Serena Giannelli; Simone Bido; Luca Massimino; Federica Ungaro; Pietro Giuseppe Mazzara; Patrizia D’Adamo; Gabriele Lignani; et al. (Nature Communications, 2022)
Dravet syndrome is a devastating epileptic encephalopathy caused by Scn1a gene haploinsufficiency. Exploiting a novel knock-in mouse model, here the authors show that restoring Scn1a expression after symptom onset is sufficient to rescue main phenotypic manifestations of the syndrome.